Global, regional, and national trends in depressive disorder prevalence and DALYs among women of childbearing age from 1990 to 2021 and projections to 2040: a comprehensive analysis from 1990 to 2021 - Yuhang Yang; Yuyuan Hu; Yuan He; Wei Zhang; Jinghan Jia; Yibo Xu; Yan Li; Jinxi Wang (Frontiers in Global Women's Health)
PurposeThis study aims to explore global, regional, and national trends in the prevalence of depression and disability-adjusted life years (DALYs) among women of childbearing age from 1990 to 2021, as well as to project future trends from 2022 to 2040.MethodsThis research analyzes the prevalence of depression and Disability-Adjusted Life Years (DALYs) among Women of Childbearing Age (WCBA) using data from the Global Burden of Disease (GBD) database, covering the period from 1990 to 2021. We evaluate trends in the burden of depression in WCBA through estimated annual percentage change (EAPC) and percentage change, as well as annual percentage change (APC) and average annual percentage change (AAPC) derived from Joinpoint regression analyses. Additionally, we employ age-period-cohort modeling to provide a more comprehensive evaluation of the prevalence of WCBA and the burden of DALYs, including future projections.ResultsIn 2021, it was estimated that there were 121.24 million cases of depression among women of childbearing age worldwide, with disability-adjusted life years (DALYs) accounting for 21.04 million cases. When compared to figures from 1990, these numbers indicate percentage increases of 68% and 69%, respectively. Moreover, despite an overall increase in both global prevalence and DALY rates, this rise was not considered statistically significant, as reflected by an estimated annual percentage change (EAPC) of −0.02 (95% confidence interval: −0.17 to 0.13) for prevalence and −0.06 (95% CI: −0.24 to 0.12) for DALYs. Furthermore, the average annual percentage change (AAPC) was computed to be 0.4789 (95% CI: 0.3289–0.6295; P < 0.001) for prevalence and 0.524 (95% CI: 0.3756–0.6725; P < 0.001) for DALYs. Projections made using our Bayesian age–period–cohort (BAPC) model suggest that we can expect a considerable increase in the global prevalence of depression and DALY rates among women of childbearing age by the year 2040.